ORIENTASI KRITIK SASTRA “PUISI” DALAM RUBRIK BUDAYA SURABAYA POST - Ni Nyoman Tanjung Turaeni (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study aims to reveal the types of literary criticism "poetry" which was published in Surabaya Post. The data source of this research is an article or writing about literature, especially poetry criticism contained in Surabaya Post in 1991-2000. The method used is analytical description. The data collection was done by using record (copy) assisted with the approach reception. The results showed that the conception of the relationship of literature, literary criticism published in Surabaya Post formulated four approaches namely, objective approach is an approach that focuses only on the literary work itself; expressive approach that approach gives more attention to the author's literary work (author); mimetic approach is more focused approach to the universe or society, and a pragmatic approach is the approach that pays more attention to readers of literary works displayed in literary criticism in Surabaya Post in 1991-2000, especially poetry.